Speech reading discrimination of homophenes - GA, Latte (Journal of All India Institute of Speech and Hearing)
One particular area of research in speech reading relates to the analysis of conruslons among visually perceived speech sounds. These visually confusable groups of sound are called ’Homophenes’.